PENGARUH ARUS KAS OPERASI, BELANJA MODAL, DAN DIVIDEND PAYOUT RATIO TERHADAP PREDIKSI LABA PADA PERUSAHAAN YANG TERDAFTAR DI INDEKS LQ 45 TAHUN 2011-2015 - Elfindari, Puput; Lautania, Maya Febrianti (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2016)
This study aimed to examine the effect of operating cash flow, capital expenditures, and dividend payout ratio on earnings predictions on companies listed in the LQ 45 2011-2015.Secondary data used were obtained from the financial statements published by the Indonesia Stock Exchange which is the reference center of the capital market in Indonesia. Type of study used in this study is hypothesis testing by purposive sampling method. There are 65 samples of data which is the object of research. The study's hypotheses were tested using multiple linear regression.The results of this study showed that simultaneous variable operating cash flow, capital expenditures, and dividend payout ratio affect the prediction of future earnings. Partially showed that (1) Operating cash flow significantly influence predictions of future earnings, (2) capital expenditures significantly influence predictions of future earnings, (3) dividend payout ratio significantly influence the future earnings forecast.Keywords Operating Cash Flow, Capital Expenditure, Dividend Payout Ratio and Earnings Prediction